British fascism after the Holocaust : from the birth of denial to the Notting Hill riots 1939-1958 - Mulhall, Joe (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book explores the policies and ideologies of a number of individuals and groups that attempted to re-launch fascist, antisemitic, and racist politics in the wake of World War II and the Holocaust. Despite the leading architects of fascism being dead, and the newsreel footage of Jewish bodies being pushed into mass graves seared into societal consciousness, fascism survived World War II and, though changed, survives to this day. Britain was the country that 'stood alone' against fascism, but it was no exception. This book treads new historical ground and shines a light onto the most understudied period of British fascism, whilst simultaneously adding to our understanding of the evolving ideology of fascism, the persistent nature of antisemitism, and the blossoming of Britain's anti-immigration movement. This book will primarily appeal to scholars and students with an interest in the history of fascism, antisemitism and the Holocaust, racism, immigration, and post-war Britain"--
The Unbroken Thread: British Fascism during World War II -- 'Wir kommen wieder': The Re-emergence of Fascism 1945- -- A Jewish Invention?: The Birth of Holocaust Denial -- Europe-a-Nation: Transnational Ideologies -- King, Country and Empire: Traditional Nationalist Ideologies -- Windrush to Notting Hill: Race and Reactions to Non-White Immigration -- A Relationship in Hate: Postwar Transatlantic Fascist Networks.
OCLC-licensed vendor bibliographic record.
Keywords: Fascism -- Great Britain -- History -- 20th century; Antisemitism -- Great Britain -- History -- 20th century; Racism -- Great Britain -- History -- 20th century; Great Britain -- Race relations -- History -- 20th century; Great Britain -- Politics and government -- 20th century; POLITICAL SCIENCE / Political Ideologies / Fascism & Totalitarianism; POLITICAL SCIENCE / Political Process / Political Parties; POLITICAL SCIENCE / Political Process / Leadership